2010
DOI: 10.1007/s10845-010-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

An analysis on effects of information security investments: a BSC perspective

Abstract: With the growing importance of information security due to the arrival of information society and the spread of the internet, information security is emerging as a tool to guarantee competitive advantage and is at the same time an indispensable requirement for stable business execution for companies and organizations. Additionally, the value of tangible and intangible assets that need to be protected as components of corporate assets are on the rise, where the importance of efficient and effective information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Then, they presented some advisable methods for investing in IT security. Within the changing corporate business environment, Kong et al (2012) analyzed the information security investment strategies and performance from a balanced score card perspective by considering the characteristics of information security investment. Bojanc et al (2012) proposed a mathematical model to optimize the information security investment evaluation and decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, they presented some advisable methods for investing in IT security. Within the changing corporate business environment, Kong et al (2012) analyzed the information security investment strategies and performance from a balanced score card perspective by considering the characteristics of information security investment. Bojanc et al (2012) proposed a mathematical model to optimize the information security investment evaluation and decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because, as the biggest barrier to the efficiency of information security, an organization regards information security activities not as an investment but as a cost. The members of an organization have neither the proper awareness nor share the necessity of information security activities, instead regarding information security activities as little more than troublesome, inconvenient procedures, thereby failing to be motivated to conduct information protection activities [5]. Regarding the goal and necessity of the adoption and management of information technologies, the members of an organization have a high awareness of such necessity and performance, but a low awareness of the necessity of the corresponding investment, thereby they fail to facilitate such activities.…”
Section: Theoretical Background 1 Previous Researches Related Tomentioning
confidence: 99%
“…Solving (9), we obtain that     for four cases in Table 1. 10 shows the average cost in (8). In Fig.…”
Section: Exponential Distributionmentioning
confidence: 99%
“…Bodin et al showed how a chief information security officer can apply the analytic hierarchy process (AHP) to determine the best way to spend a limited information security budget [7] . Kong et al evaluated information security investments from a BSC perspective [8] .…”
mentioning
confidence: 99%